Analysis of the Implementation of Marketing Communication Management MyValue Application Building Customer Relations Hotel Santika Radial Palembang - Darmawan, Wawan; Caropeboka, Ratu Mutialela; Isnawijayani; Misnawati, Desy (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study was to determine the application of marketing communication management for the MyValue application to build customer relations for Hotel Santika Radial Palembang. Done to maintain a more advanced competitiveness and the company tries to pay attention to relationships with customers. Efforts to build relationships with prospective customers and customers and companies are analyzed using marketing communication studies. The research method uses qualitative research methods. Sources of data using observation data and in-depth interviews with research informants related to research. The results of research on marketing communication management for the MyValue application to build hotel customer relations are carried out by optimizing marketing communications by implementing a promotional mix including advertising, personal selling, sales promotion, public relations and direct marketing to achieve marketing success. And the implementation of the implementation of marketing communications indirectly forms a brand image that is attached to society.